A short review on regulation of stability of aqueous suspensions of carbon nanotubes - M. V. Manilo; N. I. Lebovka; S. Barany (Хімія, фізика та технологія поверхні, 2020)
This review analyses the authors’ recent and related works on electrokinetic properties and colloidal stability of aqueous suspension of multiwalled carbon nanotubes (CNTs) in the presence of surfactants and nanoparticles. Selected adsorptive properties of carbon nanotubes are also considered.